Rytinių šiaurės žemaičių fonologinė sistema: mitai ir tikrovė - Murinienė, Lina (Baltistica, 2010)
The North-Eastern Žemaitian phonology: Myths and reality It has been commonly believed that the North-eastern Žemaitian dialects form a specific border dialect with their unique characteristics of vocalism and prosody. The purpose of the research is to separate facts from assumptions and to dispel myths concerning the stress retraction, the secondary stress, the contrast of phonemes /i/ : /ẹ/ and /u/ : /ọ/ at the end of the word and et cetera, in other words, to identify the phonological elements, examine their interrelationship and give an exhaustive description of the phonological system of the dialect employing instrumental and statistical methods. The findings from the instrumental and statistical research have lead to the following conclusions: 1. The shifted secondary stress is regularly used in long endings containing a long vowel or a pure diphthong. In the south-western part of the dialect the secondary stress is not realized in long endings, containing a semi-diphthong (i.e., a vowel + sonorant cluster). This tendency can be observed throughout the whole area of the dialect. 2. When the stress is retracted to the beginning of the word, the secondary stress is preserved consistently. 3. A more consistent retraction of stress from acute final syllables is observed only in ā and ē stems of present and past tense forms in the first and second person singular. From the diachronic point of view, this is a new morphological phenomenon. 4. The distinctive accent contrast is realized in long stressed syllables; it is neutralized in the endings in which the archiprosodeme is represented by the acute. In the retracted-stress syllables the contrast of accents is consistently maintained only in the north-eastern part of the dialect. 5. The contrast of phonemes /i/ : /ẹ/ and /u/ : /ọ/ is systematically realized at the end of a word. In the stem this contrast is neutralized: the realization of high or mid-open phonemes depends upon the vocalism of the following syllable (the regressive assimilation of vowels). 6. The phonological vowel system of the dialect consists of 14 phonemes: /i·, u·, ie, uo, (ẹ·), (ọ·) (e·), a·, i, u, ẹ, ọ, (e), a/. The long /ẹ·/ and /ọ·/ belong to the periphery of the system. The open front phonemes /e·/, /e/ are not found in the system of vowels of the south-eastern fringe of the dialect.